Does the fulfillment of contraceptive method preferences affect contraceptive continuation? Evidence from urban Kenya, Nigeria, and Senegal - Carolina Cardona; David Bishai; Phil Anglewicz (Demographic Research)
BACKGROUND: Although interest in patient-centered family planning measures is growing, little is known about women’s preferences for contraceptive methods and whether these preferences influence contraceptive behaviors. OBJECTIVE: We assessed whether the fulfillment of contraceptive preferences affected women’s decisions to continue, switch, or stop using contraception. METHODS: Data came from a panel of urban Kenyan, Nigerian, and Senegalese women collected between 2010–2015. Women who were not using contraception at baseline and intended to use reported their preferred contraceptive method, and then at the second round reported their contraceptive use, which permits us to measure whether they fulfilled their baseline preference. We then examined whether fulfilling their contraceptive preference was associated with the decision to continue, switch, or stop using contraception by the third round by estimating a set of probit and bivariate probit models. RESULTS: After controlling for individual, household, and health system characteristics, women with fulfilled contraceptive preferences were 25 percentage points less likely to stop or switch contraceptive methods than women with unfulfilled contraceptive preferences. CONCLUSIONS: Fulfilling contraceptive preferences is associated with later contraceptive behavior, which demonstrates the importance of these preferences for achieving family planning goals. CONTRIBUTION: This study is important because it is the first research looking at the relationship between the fulfillment of contraceptive method preferences and contraceptive continuation in low- and middle-income countries. Women have a high probability of adhering to their contraceptive method when using a method that satisfies their contraceptive preferences.